1995
DOI: 10.1046/j.1525-1438.1995.05020081.x
|View full text |Cite
|
Sign up to set email alerts
|

Weekly cisplatin +- glutathione in relapsed ovarian carcinoma

Abstract: On the basis of experimental data showing the efficacy of glutathione (GSH) as a protective agent on cisplatin-induced neurotoxicity and the clinical evidence of the low incidence of neurotoxicity in high-dose cisplatin + GSH treated patients we evaluated the neuroprotective effect of GSH in a randomized phase II study. Thirty-three patients with relapsed ovarian cancer after a disease-free interval of at least 1 year and a cumulative dose of prior cisplatin ranging 450-650 mg m-2 were randomized to receive ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 8 publications
0
27
1
Order By: Relevance
“…To date, the most effective approach to management of drug-induced neuropathy has been that of limiting the total dose, or reducing individual doses or even discontinuing the neurotoxic drugs at appearance of moderate symptoms (Ocean and Vahdat, 2004). In order to prevent or mitigate chemotherapy-induced neuropathy, drugs such as amifostine (Openshaw et al, 2004), reduced glutathione (Colombo et al, 1995), calcium and magnesium infusions, glutamine Vahdat et al, 2001), acetyl-L-carnitine (Bianchi et al, 2005) or vitamin E (Pace et al, 2003;Argyriou et al, 2005) have been tested, but results have not always been satisfactory (Umapathi and Chaudhry, 2005;Albers et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the most effective approach to management of drug-induced neuropathy has been that of limiting the total dose, or reducing individual doses or even discontinuing the neurotoxic drugs at appearance of moderate symptoms (Ocean and Vahdat, 2004). In order to prevent or mitigate chemotherapy-induced neuropathy, drugs such as amifostine (Openshaw et al, 2004), reduced glutathione (Colombo et al, 1995), calcium and magnesium infusions, glutamine Vahdat et al, 2001), acetyl-L-carnitine (Bianchi et al, 2005) or vitamin E (Pace et al, 2003;Argyriou et al, 2005) have been tested, but results have not always been satisfactory (Umapathi and Chaudhry, 2005;Albers et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…GSH is reported to diminish cisplatin-induced neurotoxicity, and patients treated with cisplatin in combination with GSH (doses ranging from 1.5 to 3 g/m 2 ) exhibit a less severe neuropathic syndrome with no negative interference of its anticancer activity in these patients (Cavaletti et al, 1996;Colombo et al, 1995;Di Re et al, 1993). Experimental studies performed on rats have shown that GSH provides protection against the cisplatininduced slowing of sensory nerve conduction velocity without interfering with the antitumour ecacy of this drug (Hamers et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The trials all reported a reduction in neurotoxicity, albeit the degree of protection varied greatly. [218][219][220][221][222][223][224] In a large randomized, double-blind, placebo-controlled trial to investigate the ability of glutathione to reverse the neuropathy associated with paclitaxel/carboplatin combination treatment; however, glutathione did not prevent CIPN. 225 Several small-clinical trials also demonstrated that vitamin E might have efficacy to decrease the incidence or severity of CIPN following paclitaxel or cisplatin treatment [226][227][228][229] ; however, a phase III clinical trial failed to reproduce the beneficial effects of the putative antioxidant.…”
Section: Nitroxidative Stressmentioning
confidence: 99%